ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ignatia, Gresica; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2024)
This study aims to analyze the effect of capital structure, firm growth and firm size on firm value of company listed in the Indonesian Stock Exchange (IDX) with managerial ownership as moderating variable. The study period from 2018 to 2020. The study used a quantitative method with multiple linear regression analysis. The study sample was taken based on purposive sampling method consisted of sixty five manufacturing companies. The data collected, was processed using EViews v.12.0 program. The results of this study show that the capital strucutre dan firm growth has significant positive effect on firm value. Menawhile, the results of firm size has no significant effect on firm value. This study also analyze that moderating variable of managerial ownership is not capable of moderated all variables of capital structure, firm growth dan firm size on firm value.